Pré-construído e Memória: análise discursiva dos Códigos de Ética dos Jornalistas Brasileiros - Soares, Fabiana (2020)
This thesis work focuses on the discursivity of the Codes of Ethics developed for Brazilian journalists, trying to understand how they produce effects of meaning in journalistic discourse. As a result, the theoretical contribution presented in this work comes from the French Discourse Analysis as proposed by Michel Pêcheux, as well as the Brazilian approach, developed by Eni Orlandi and her research group. Discourse Analysis is established by the relationship between the fields of Linguistics, Historical Materialism and Psychoanalysis, from which it is derived. As an intermediate discipline, it is mainly concerned with speech. We understand that questions about journalistic ethics in the reports published since the 1940s, or even earlier, led to the creation of the first Code of Ethics, reformulated in 1968, 1986 and 2007. Consequently, while having as a corpus of the Codes mentioned above, we propose here a set of articles launched in the press during the periods preceding and following each Code, so as to demonstrate the way in which they are organized. In this regard, we will examine the conditions of production of these Codes, highlighting the historical context of each period. In addition, we offer a discussion of the historical path of press laws and decrees in Brazil, which we understand, discursively, as preconstructed of the referred Codes. By focusing on materialities, we mobilize the essential notions of Discourse Analysis, namely: archive, historicity, discursive memory, conditions of production, among others. These concepts are related to the theories of Journalistic Ethics, as discussed by Rogério Christofoletti (2008), Francisco Karam (2014), Eugênio Bucci (2000), Mayra Rodrigues Gomes (2002) and Luciene Tófoli (2008).